Market Orientation on Export Marketing Performance: The Role of Disruptive Innovation and Flexibility Supporting SDGs 8 and 9 - Rohwiyati Rohwiyati; Tulus Haryono; Ahmad Ikhwan Setiawan; Lilik Wahyudi; Tri Darsono; Sulistya Sulistya (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: How customer orientation and competitor orientation influence the export marketing performance of coffee-exporting micro, small, and medium-sized enterprises (MSMEs), while assessing the mediating role of disruptive innovation and the moderating role of organizational flexibility. The study also highlights the relevance of these capabilities to SDG 8 and SDG 9 through inclusive export growth and innovation-driven competitiveness. Method: A quantitative explanatory design was employed using survey data from 116 coffee-exporting MSMEs in Central Java, Indonesia, selected through purposive sampling. The relationships among the constructs were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3. Results: Customer orientation significantly improved export marketing performance, whereas competitor orientation had no significant direct effect. Both customer and competitor orientation significantly promoted disruptive innovation, which in turn enhanced export marketing performance. Disruptive innovation significantly mediated both market-orientation dimensions, and flexibility strengthened its positive effect on export marketing performance. Novelty: Integrating disruptive innovation as a mediating mechanism and flexibility as a boundary condition in a single export-marketing model for coffee MSMEs. The model explains how market intelligence can be converted into adaptive innovation and stronger export outcomes, offering an SDG-aligned pathway for resilient MSME internationalization.